Perancangan Produk Furnitur Foldable Untuk Ruang Keluarga Multifungsi Di Perumahan Tipe 36 (Studi Kasus Perumahan Citra Bulan Indah, Klaten) - Flamboyan El Grascia; Marcellino Aditya; Purwanto Purwanto (Penerbit Itenas, 2025)
Population growth in Klaten City has led to an increase in the need for decent housing, especially in type 36 housing which is often built as a solution to land limitations. The living room in this type of house is often used as a multifunctional room used for various activities. Activities carried out such as studying, ironing, dining room, family room, to storing occupants' belongings, so that this room is known as a multifunctional family room. This condition raises challenges in terms of space efficiency and comfort, because the furniture available on the market is not yet able to support several activities carried out simultaneously. The purpose of this design is to create a multifunctional furniture product that can not only be adjusted to the needs of occupant activities, but is also easy to fold (foldable) and provides additional storage space. This design has benefits as a reference for adaptive design solutions that support optimal space utilization in small-sized homes. The design process is carried out through field studies, user needs analysis, concept development, and final design evaluation. The SCAMPER method is used as an idea exploration approach to produce various design alternatives. The final result of this study is a multifunctional folding furniture product that is ergonomic, compact, and pays attention to aspects of strength and material safety, so that it can be used flexibly in the long term. The novel value of this research lies in the combination of learning and ironing functions in one furniture unit that can be folded and moved easily, and supports space efficiency in a minimalist residential environment.